The dilemma of colonial transportation on the Lower Niger and Benue Rivers 1879-1960 - Ali, Anthony Danladi (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
The aim of this study is to investigate the dilemma of transportation on the Lower Niger and Benue Rivers in Nigeria in the Hey days of European commercial water traffic in the period 1879 to 1960. This study finds out that the Lower Niger and Benue Rivers experienced a heavy traffic during the high water season of June to November but in the dry or low water season in December to May, vessels could not come up river from the open sea at Burutu. This paper concludes that the seasonal nature of transportation on the Lower Niger and Benue Rivers in the colonial period was a set-back to serious and effective transportation. This study is significant because in the Hey Day of commercial water traffic on the Lower Niger River, over ten steamers or Vessels or boats plied up to the confluence of the Lower Niger and Benue Rivers at Lokoja daily from Burutu. The study adopts historical methodology using primary sources such as archival documents and oral interviews and secondary sources which involve the extensive use of published books and dissertation.